Line x tester analysis for combining ability in Indian mustard [Brassica juncea (L.) Czern & Coss] (Journal of Oilseed Brassica, 2025)
Line × tester analysis was carried out to estimate combining ability of 36 hybrids developed by crossing 9 lines with 4 testers of Indian mustard. Estimates of GCA effects indicated that Kranti, RH-749, Pusa Mustard-30 and Pusa Mahak and Tester, PM-27 were good general combiner. Significant SCA effects for seed yield per plant and other attributing traits in desirable direction were recorded in a series of hybrids and a close association between SCA effects and heterosis was observed amongst the best hybrids identified on the basis of SCA effects. The three hybrids; PM- 30 x CS 54, NRCHB 101 x PM 27, RH 749 x JM 1, IC-597889 x JM-1 and RH-30 x CS-54 exhibited highly significant SCA effects and higher per se performance for seed yield and important traits. The high yielding cross combinations can be further exploited for improving the seed yield by development superior genotypes.